Silicate-Enhanced Heterogeneous Flow-Through Electro-Fenton System Using Iron Oxides under Nanoconfinement - Guo, Dongli; Yanbiao Liu; Ji, Haodong; Chong-Chen Wang; Bo Chen; Chensi Shen; Fang Li; Wang, Yongxia; Ping Lu; Liu, Wen (Environmental Science & Technology, 2021)
Herein, a silicate-enhanced flow-through electro-Fenton system with a nanoconfined catalyst was rationally designed and demonstrated for the highly efficient, rapid, and selective degradation of antibiotic tetracycline. The key active component of this system is the Fe2O3 nanoparticle filled carbon nanotube (Fe2O3-in-CNT) filter. Under an electric field, this composite filter enabled in situ H2O2 generation, which was converted to reactive oxygen species accompanied by the redox cycling of Fe3+/Fe2+. The presence of the silicate electrolyte significantly boosted the H2O2 yield by preventing the O–O bond dissociation of the adsorbed OOH*. Compared with the surface coated Fe2O3 on the CNT (Fe2O3-out-CNT) filter, the Fe2O3-in-CNT filter demonstrated 1.65 times higher kL value toward the degradation of the antibiotic tetracycline. Electron paramagnetic resonance and radical quenching tests synergistically verified that the dominant radical species was the 1O2 or HO· in the confined Fe2O3-in-CNT or unconfined Fe2O3-out-CNT system, respectively. The flow-through configuration offered improved tetracycline degradation kinetics, which was 5.1 times higher (at flow rate of 1.5 mL min–1) than that of a conventional batch reactor. Liquid chromatography–mass spectrometry measurements and theoretical calculations suggested reduced toxicity of fragments of tetracycline formed. This study provides a novel strategy by integrating state-of-the-art material science, Fenton chemistry, and microfiltration technology for environmental remediation.